Diseño de un manual de distribución de funciones para el área de limpieza de la ESPAM MFL. - Espinel Vera, Jorge Yull (2016)
Research was carried out in the agricultural Polytechnic School of Manabí MFL, located on the site specifically lemon in the cleaning area, with the goal of designing a manual distribution of functions for the cleaning of the MFL spam area, which defines the activities of the personnel that work in this unit. To comply with the data collection methods were used: descriptive study, methodology qualitative, inductive, deductive, allowing to carry out the objectives. They used techniques as the interview and survey, was the observation that it was the spontaneously get information to indicate if study design is safe. Also investigated the causes originating the problem to produce chips of registration where it was classified and store information. Then proceeded to execute the objectives allowing to diagnose the organizational structure of the cleaning area through an interview performed to the Director of human talent in this way identified functions assigned as cargo, required profile and the responsibilities of each of them. Then they conducted a survey aimed at workers in the cleaning area where it was verified if they know which is the correct execution of activities, responsibilities and competencies corresponding to each job, finally developed a manual distribution of functions applicable to the activities of the area in which it was found profiles, activities, identification of cargo duties and responsibilities of the employee.